Investigation the use of oxygen and carbon isotopes and sclerochronology on Turbo sarmaticus and Donax serra for palaeoenvironment reconstruction at Pinnacle Point, South Africa - Galimberti, Mariagrazia (Department of Archaeology, 2014)
Includes bibliographical references (p. 241-272).